Análise Aprimorada das Percepções dos Usuários por Meio de Abordagens de Processamento de Linguagem Natural - Machado, Ana Cláudia; Prenassi, Gabriel; Tuler, Elisa; Rocha, Leonardo (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2025.13901, 2025)
In this article, we present a framework for analyzing users’ textual comments, going beyond the evaluation carried out using the System Usability Scale, a traditional methodology for system assessment. The framework performs textual analysis through Topic Modeling, Text Summarization, and Sentiment Analysis. Topic Modeling identifies semantic topics in the comments, while Text Summarization generates summaries of each topic, enabling explainability. Sentiment Analysis, in turn, categorizes the sentiment of each topic, identifying its polarity. We propose an intuitive visual interface and apply our framework in a real-world scenario, where it enabled more accurate feedback.